Bioleaching Ability of Fungi Isolated from an Indonesian Sulfurous River Sediment - Serafica Btari Christiyani Kusumaningrum; I Wayan Warmada; Wahyu Wilopo; Endah Retnaningrum (Universitas Gadjah Mada, 2020)
The unique characteristics of sulfurous river sediment located in Ungaran, Indonesia, are a reservoir of novel fungi with manganese bioleaching properties. Fungi are known to produce metabolic organic acids that have a potential for the industrial application of leaching metal from the ores. This application has high advantages, including low cost, low energy, and creates minimal environmental damage. Therefore, this research was performed to analyze the manganese bioleaching activities of two fungal isolates (KA2B2 and KB4B) from Indonesian sulfurous river sediment on pyrolusite and determine their phenotypic characters. These activities were investigated in terms of changes in fungal biomass, soluble manganese concentration, pH reduction, and organic acid production during 16 days of leaching. Soluble manganese concentrations were measured by atomic absorption spectrometry (AAS), whereas organic acid concentrations were analyzed by high-performance liquid chromatography (HPLC). According to bioleaching investigations, KA2B2 strain was more efficient than KB4B1 strain in extracting manganese from 0.02 g/cm3 pyrolusite. It also produced higher levels of organic acids, such as oxalic acid and citric acid, than KB4B1 strain, proving that strain of KA2B2 could be used to extract manganese from pyrolusite. Based on the phenotypic characters, both strains were identified as genus Penicillium.